2015
DOI: 10.1002/ange.201506690
|View full text |Cite
|
Sign up to set email alerts
|

Perovskites with the Framework‐Forming Xenon

Abstract: The Group 18 elements (noble gases) were the last ones in the periodic system to have not been encountered in perovskite structures.W eh erein report the synthesis of an ew group of double perovskites KM(XeNaO 6 )( M= Ca, Sr,B a) containing framework-forming xenon. The structures of the new compounds,like other double perovskites,are built up of the alternating sequence of corner-sharing (XeO 6 )and (NaO 6 ) octahedra arranged in athree-dimensional rocksalt order.The fact that xenon can be incorporated into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In contrast, charge imbalance in cubic perovskite induced by substitution of Ti 4+ for Cr 3+ is compensated by the emergence of oxygen vacancies, without changes at the A-site: Ti 4+ + ½O 2-→ Cr 3+ + ½(□) 0 . In summary, taking into account the unprecedented structural flexibility of the perovskite B-site (Mitchell 2002;Britvin et al 2015), this substitution scheme alone provides a mechanism for incorporation of almost any element into the framework of natural perovskites. The stability of such disordered structures up to very high pressure…”
Section: Oxygen Vacancies: a Gateway To Compositional Flexibility Of Cubic Perovskitementioning
confidence: 99%
“…In contrast, charge imbalance in cubic perovskite induced by substitution of Ti 4+ for Cr 3+ is compensated by the emergence of oxygen vacancies, without changes at the A-site: Ti 4+ + ½O 2-→ Cr 3+ + ½(□) 0 . In summary, taking into account the unprecedented structural flexibility of the perovskite B-site (Mitchell 2002;Britvin et al 2015), this substitution scheme alone provides a mechanism for incorporation of almost any element into the framework of natural perovskites. The stability of such disordered structures up to very high pressure…”
Section: Oxygen Vacancies: a Gateway To Compositional Flexibility Of Cubic Perovskitementioning
confidence: 99%
“…Skutterudites can be considered as non-stoichiometric A-site vacant quadruple perovskites □□BB′X 6 . The quadruple perovskite KCa(NaXe)O 6 with Na + and Xe 8+ ordered on B and B′ sites synthesized by Britvin et al (2015) is possibly important with respect to terrestrial noble gas geochemistry. Britvin et al (2015) have suggested that the observed depletion in Xe in the Earth's atmosphere could result from trapping of Xe in lower mantle perovskites.…”
Section: Stoichiometric Double Perovskitesmentioning
confidence: 99%
“…Much of this work was driven by the observation that the perovskite structure is extremely 'flexible' with regard to cationic and anionic replacements and tolerance to ionic defects. Unlike many other structural types, every element of the periodic table, including the noble gases (Shcheka and Keppler, 2012;Britvin et al, 2015;, can be found in some variant of perovskite-structured compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Noble gas or aerogen-bonding interactions were termed as such in 2015 [ 81 ], and afterward, several experimental [ 82 , 83 , 84 ] and theoretical [ 85 , 86 , 87 , 88 , 89 ] investigations have appeared in the literature describing and confirming their relevance in X-ray structures and also its interplay with other interactions. The purpose of this short review is to examine the recent research on NgB interactions, including theoretical and experimental investigations.…”
Section: Introductionmentioning
confidence: 99%